Potentials of Multicultural Education in Communal Conflict Areas - Syamsul Kurniawan; Muhammad Miftah (FITK UIN Walisongo, 2021)
This study focuses on understanding communal conflicts in Indonesia, which are triggered by stereotyping. Indonesians have undergone communal conflicts, especially in the late 1990s. The conflicts were mainly religious and ethnic, suggesting serious tensions in stereotyping between religious and ethnic groups. In this case, the paper seeks to underline the importance of multicultural education in the school context. Education is considered having a strategic role in building positive circumstances among people. Multicultural education is expected to minimize the possibility of building negative stereotyping of one person against another, which could cause conflict. This qualitative study incorporates a literature review of multicultural education and communal conflicts in the Indonesian context.